6. STUDI PERBANDINGAN INTEGRITAS PENYELENGGARA PEMILU DALAM PELAKSANAAN PEMILIHAN UMUM GUBERNUR DAN WAKIL GUBERNUR JAWA TENGAH DAN MALUKU TAHUN 2013 - Nur Hidayat Sardini (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
This research compares the integrity of election officials in Central Java Province with those who are in Maluku Province on carrying out gubernatorial elections in 2013. The integrity of election officials is measured by basic principles of ethics and conduct as it is defined on Joint Regulation of General Election Commission, General Election Supervisory Agency, and Honorary Board of General Election Organizers Number 13, 11, 1 of 2012 on Code of Ethics For General Election Organizer. The study uses qualitative method of research. It examines documentary data and information related to code of ethics infringements reports conducted by General Election Commission or General Election Supervisory Agency which are connected to their work on carrying out gubernatorial elections in 2013. The research shows that there is no lack of integrity of election organizer in Central Java Province on carrying out gubernatorial elections in 2013. On the contrary, the study found that the election organizer in Maluku involved in some code of ethics infringements on their work.